STUDY AND FORMATION OF CULINARY NAMES IN ENGLISH AND UZBEK LANGUAGES (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Head of the English language club of the "Barkamol Avlod" children's school in Termiz city